Realitas Pengamalan Nilai-Nilai Pancasila sebagai Kontrol Sosial pada Masyarakat Adat Lokal Tanah Luwu - Assaad, A. Sukmawati; Zainuddin, Fauziah; Hasyim, Baso (Palita: Journal of Social Religion Research, 2021)
Abstract[English]:Practicing the values of Pancasila is very urgent to be realized by every citizen of the community so that in interacting with one another there is harmony in life. Pancasila as social control in the plurality of tribes, cultures, races, religions, languages in the Republic of Indonesia contains religious or spiritual values, ethical-moral values, social values, political values and the value of justice as goals. The local indigenous community of Tanah Luwu is a diverse society that can be said to be a miniature of Indonesia. There are Luwu tribe, Bugis tribe, Toraja tribe, Makassar tribe, Javanese tribe, Balinese tribe, Lombok tribe, Timor tribe and others. The religion also consists of Islam, Christianity, Hinduism, Buddhism, Confucianism, besides that the Land of Luwu has a wide area and includes trasmigran area so that the range of conflict occurs.Abstrak[Indonesia]:Pengamalan nilai-nilai Pancasila sangat urgen untuk direalisasikan oleh setiap orang warga masyarakat agar dalam berinteraksi satu sama lain terjalin harmonisasi hidup. Pancasila sebagai kontrol sosial dalam kemajemukan suku, budaya, ras, agama, bahasa di negara Republik Indonesia mengandung nilai-nilai agama atau spiritual, nilai etika- moral, nilai sosial, nilai politik dan nilai keadilan sebagai tujuan. Masyarakat adat lokal Tanah Luwu adalah masyarakat yang beragam bisa dikatakan miniatur Indonesia. Terdapat suku Luwu, suku Bugis, suku Toraja, suku Makassar, suku Jawa, suku Bali, suku Lombok, suku Timor dan lainnya juga agamanya terdiri dari Islam, Kristen, Hindu, Budha, Konghucu, di samping itu Tanah Luwu memiliki wilayah yang luas dan termasuk daerah transmigran sehingga rentang terjadi konflik.